EFEKTIVITAS EKSTRAK BEBERAPA BAHAN NABATI LOKAL SEBAGAI PESTISIDA NABATI DALAM MENGENDALIKAN HAMA BUBUK JAGUNG (Sitophylus zeamays) - Yosefus F. da-Lopes; Welianto Boboy (Politeknik Pertanian Negeri Kupang, 2008)
Effectiveness Several Local Plants Extracts as Botanic Pesticide in Controlling Sitophylus zeamays. The research aimed to know the effectiveness of papaya leaves, piper betle leaves, and nimba leaves, as botanic pesticide in order to control Sitophylus zeamays. The research was arranged in randomized block design, by three replications. The treatments studied consisted of control (without botanic pesticide), extract of papaya leaves, nimbi leaves, and piper betle leaves. Parameter measured consisted of severity and population density of S. zeamays. Data were analyzed using analysis of variance, and were continued with Duncan Multiple Range Test to find out the difference of influence at treatments tried. The results indicated that using of local plants as botanic pesticide affected to severity and population density of S. zeamays (probability < 0.05). Those botanic pesticides were sufficient influential to control S. zeamays. These were performed by level decrease of corn weight. Population density of S. zeamays was still showing hard attack; however, those botanic pesticides are useable in depressing development of S. zeamays.Keywords: S. zeamays, papaya, piper betle, nimba